2010
DOI: 10.1103/physrevc.82.034306
|View full text |Cite
|
Sign up to set email alerts
|

Canonical-basis time-dependent Hartree-Fock-Bogoliubov theory and linear-response calculations

Abstract: We present simple equations for a canonical-basis (Cb) formulation of the time-dependent Hartree-FockBogoliubov (TDHFB) theory. The equations are obtained from the TDHFB theory with an approximation that the pair potential is assumed to be diagonal in the Cb. The Cb formulation significantly reduces the computational cost. We apply the method to linear-response calculations for even-even light nuclei and demonstrate its capability and accuracy by comparing our results with recent calculations of the quasiparti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
229
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 168 publications
(242 citation statements)
references
References 28 publications
7
229
0
Order By: Relevance
“…Jz, 24.30.Cz, 27.60.+j The low-energy dipole states, often referred to as the pygmy dipole resonance (PDR), have attracted recent experimental [1][2][3][4][5][6] and theoretical interests [7][8][9][10][11][12] (see also the recent review [13] and references therein). It is also of significant astrophysical interest, since the low-energy dipole strengths close to the neutron threshold strongly affect the astrophysical r-process nucleosynthesis [14].…”
mentioning
confidence: 99%
“…Jz, 24.30.Cz, 27.60.+j The low-energy dipole states, often referred to as the pygmy dipole resonance (PDR), have attracted recent experimental [1][2][3][4][5][6] and theoretical interests [7][8][9][10][11][12] (see also the recent review [13] and references therein). It is also of significant astrophysical interest, since the low-energy dipole strengths close to the neutron threshold strongly affect the astrophysical r-process nucleosynthesis [14].…”
mentioning
confidence: 99%
“…In several studies, it has been shown that the BCS approximation is a good compromise to take into account pairing in the mean-field framework. In particular, comparisons to QRPA calculations show a good agreement with the BCS approximation for the small amplitude motion [6,7].…”
Section: Introductionmentioning
confidence: 64%
“…[20,21]. These formulas are identical to the time dependent Hartree-Fock-Bogoliubov equations [22][23][24]. The symbol h γ denotes the Landau-Zener interaction, whileĒ γ and T γ are energy terms.…”
Section: The Landau-zener Effect and The Seniority Mixingmentioning
confidence: 91%